PHYTOTOXICITY OF WASTEWATER CONTAINING CADMIUM (Cd) USING OLEANDER - & Ridha, Zeki (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate the ability of N.oleander to remove Cadmium (Cd) from wastewater. A prolonged toxicity test was performed in a single exposure and run for 65 days with various concentrations of Cd. Plants were grown in sand medium and irrigated with simulated wastewater contaminated with Cd, using different concentrations (0, 10, 25, 50, 75 mg/L), which were chosen based on previous preliminary test. The results of physical observation of the plants didn’t show any withering symptoms. The Cd concentration in plants increased, while in water decreased. The results of plant analysis showed that Cd concentration in plant shoots (stems and leaves) was higher than that in roots for almost all exposure doses along the test duration. The concentration of Cd in water decreased significantly from the first week of the test and become (0 mg/l) on day-35 for 10 and 25 mg/l exposure doses, while exceeded the permissible limits for 50 and 75 mg/l exposure doses and were 0.14 and 0.91 mg/l, respectively. Wet weight and dry weight of Oleander decreased with increasing Cd concentration level except for 10 mg/l exposure dose where the plant wet weight and dry weight increased at the end of the test. Bioaccumulation factor (BAF) and Translocation Factor (TF) was found to be greater than 1, indicating that Oleander is a successful hyperaccumulator for Cd.